ChemInform Abstract: Understanding Automotive Exhaust Catalysts Using a Surface Science Approach: Model NOx Storage Materials. Issue 49 (3rd December 2013) - Szanyi, Janos; Yi, Cheol Woo; Mudiyanselage, Kumudu; Kwak, Ja Hun
Abstract Review: 56 refs.